2021
DOI: 10.3390/su132112180
|View full text |Cite
|
Sign up to set email alerts
|

Management Strategies and Stakeholders Analysis to Strengthen the Management and Use of Biosolids in a Colombian Municipality

Abstract: The difficulties in the management and use of biosolids in Colombia make it necessary to evaluate and analyze the factors involved through various methodologies to achieve the effective management and recycling of this type of waste. The objective of this study was to evaluate the management of sludge and biosolids from a WWTP in a Colombian municipality through the application of three methodologies (SWOT/TOWS, surveys, and stakeholder (player) weighing) for their subsequent use in agriculture. As a result, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…In 2015, about 28.8% of biosolids generated were incinerated, while 15% were used in landfill (Tessier, 2017). According to Tessier, disposal of biosolids via incineration is declining, while land application is rising in Canada (Venegas et al, 2021). This trend is related to regulatory influences and voluntary biosolids quality enhancements but has been drastically slowed down by recent media attention on the presence of PFAS in biosolids.…”
Section: Survey Of Global Biosolids Generation and Management-case St...mentioning
confidence: 99%
“…In 2015, about 28.8% of biosolids generated were incinerated, while 15% were used in landfill (Tessier, 2017). According to Tessier, disposal of biosolids via incineration is declining, while land application is rising in Canada (Venegas et al, 2021). This trend is related to regulatory influences and voluntary biosolids quality enhancements but has been drastically slowed down by recent media attention on the presence of PFAS in biosolids.…”
Section: Survey Of Global Biosolids Generation and Management-case St...mentioning
confidence: 99%
“…Regarding the application of renewable energies in Latin American countries, Horta et al [20] developed a methodology to evaluate the possibilities of integrating bioenergy projects in Latin America, the Caribbean, and Africa through a SWOT analysis. Venegas et al [21] researched biofuels' use and their waste management and recycling, focusing on a Colombian municipality. Finally, Diaz and Cilinskis [22] developed another study concern-ing Colombia using a multi-criteria analysis to define its path to decarbonization.…”
Section: Literature Overviewmentioning
confidence: 99%
“…The term "biosolids" has been adopted for treated sewage sludge more generally, as social science survey evidence suggested that it elicited a more positive perception than the word "sludge" [28,29]. Unlike for biochar, there have been numerous studies looking at its public perception [30][31][32][33][34]. This is in part because biosolid land application relies on public acceptance of key issues around its health, safety and environmental impacts.…”
Section: Definitionsmentioning
confidence: 99%